Synthesis and evaluation of 2′-dihalo ribonucleotide prodrugs with activity against hepatitis C virus. Issue 1 (1st January 2020) - Chris Krueger, A.; Chen, Hui-Ju; Randolph, John T.; Brown, Brian S.; Halvorsen, Geoff T.; Heyman, Howard R.; Li, Tongmei; Marvin, Christopher C.; Shanley, Jason P.; Voight, Eric A.; Bow, Daniel A.J.; Van Handel, Cecilia; et al.
Graphical abstract: Abstract: Hepatitis C virus (HCV) nucleoside inhibitors have been a key focus of nearly 2 decades of HCV drug research due to a high barrier to drug resistance and pan-genotypic activity profile provided by molecules in this drug class. Our investigations focused on several potent 2′-halogenated uridine-based HCV polymerase inhibitors, resulting in the discovery of novel 2′-deoxy-2′-dihalo-uridine analogs that are potent inhibitors in replicon assays for all genotypes. Further studies to improve in vivo performance of these nucleoside inhibitors identified aminoisobutyric acid ethyl ester (AIBEE) phosphoramidate prodrugs 18a and 18c, which provide high levels of the active triphosphate in dog liver. AIBEE prodrug 18c was compared with sofosbuvir (1 ) by co-dosing both compounds by oral administration in dog (5 mg/kg each) and measuring liver concentrations of the active triphosphate metabolite at both 4 and 24 h post dosing. In this study, 18c provided liver triphosphate concentrations that were 6-fold higher than sofosbuvir (1 ) at both biopsy time points, suggesting that 18c could be a highly effective agent for treating HCV infected patients in the clinic.